GEOPOLITICAL VISION OF THE PERUVIAN AMAZON AND ITS SOCIAL, ECONOMIC AND POLITICAL IMPACT - Olaya Moreno, Maximo (2021)
The Peruvian Amazon is the holder of a series of natural resources that are the nation’s economic source, representing a living habitat for a series of indigenous communities, abundant flora and fauna, and a series of rivers that make up the Amazon River. Based on its importance, this article’s main objective was to determine if there is a geopolitical strategy of the State aimed at protecting the Peruvian Amazon with respect to the social, economic and political impact it generates in Peru. The research was of a theoretical-empirical type, qualitative approach, and the research method was hermeneutical-interpretive. The population was made up of 43 investigations and 13 scientific articles, in addition to testimonies related to the international geopolitical vision. The sample consisted of 20 scientific investigations regarding the geopolitical vision of the Amazon in the social, economic and political fields, as well as the testimony of three experts in the field. Regarding the data collection techniques, the documentary analysis and the semi-structured interview were applied, using the registration sheets and the interview guide as instruments. It was found that the economic potential of this region makes it more attractive, since there is a potential in natural resources; Furthermore, the sense of belonging of the different indigenous and inter-ethnic communities and respect for their modus vivendus was evident, therefore, natural resources should be used harmoniously without harming the environment. It was concluded that the Peruvian Amazon has an important and essential role for the State due to its economic potential; However, there is still an Amazonian regional vacuum without sustainable development and with a greater impact on human development indices, as well as an empirical state without clear actions and policies to position itself geopolitically in the Amazon.